"Glimpses of the Wonderful": The Jamaican origins of the aquarium. Issue 1 (2nd January 2022) - Senior, Emily
ABSTRACT: This study addresses the well-known history of Victorian naturalist Philip Gosse's popularisation of the marine aquarium through a new lens: the period he spent in Jamaica during the 1840s. Firstly, it reveals the importance of African-Caribbean collectors and naturalists to Gosse's natural history practise and shows the impact of racialized ethnographic perspectives on Victorian natural knowledge. Secondly, it argues that Gosse's observations of marine biology in Jamaica were significant for his developing ideas about examining and displaying sea creatures and informed his designs for British aquaria. Understanding Gosse's aquatic displays as archives of living bodies sets Gosse's contribution to Victorian aesthetic, museological and technological developments in the context of his natural history work in Jamaica.